Peran Komunikasi Pembangunan dalam Membangun Desa - Winda Kustiawan; Nadya Syakilah; Melda Wati Simanjuntak; Nandini Nandini; Heny Trie Dina Aliya (Universitas 17 Agustus 1945 Semarang, 2023)
This article discusses the role of development communication in developing villages. Through a literature review and case studies, this article attempts to provide a thorough understanding of how development communication can help speed up village development processes. This article will also cover some important points such as types of development communication, effective development communication methods, obstacles that are often encountered in implementing development communication programs, and the benefits that can be obtained from using development communication in developing villages.